2021
DOI: 10.1215/00703370-9160022
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mothers' Parenting Time by Education and Work From 2003 to 2017

Abstract: Scholars have been increasingly concerned about the rise in “intensive mothering” and its implications for the well-being of children and women and for inequality more broadly. These concerns, however, reflect a key assumption: that socioeconomic disparities in mothers' parenting time observed in earlier eras have continued to grow. Using the American Time Use Survey (ATUS) from 2003–2005 and 2015–2017 (n = 13,755), we test this assumption by examining whether maternal education gaps in active time spent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 62 publications
(45 reference statements)
0
39
1
Order By: Relevance
“…The results corroborate the findings from 2006, 2012, and 2016 MICS, which found that Thai children under the age of five whose parents had higher education levels engaged in more parental interactions (81%, 96%, and 97%, respectively) [ 15 , 16 , 17 ]. Higher parental education likely creates parental awareness and responsiveness to the children’s natural needs and demand for plays [ 21 , 22 ]. Moreover, educated parents seem to have the ability to obtain specific information about their children’s health requirements [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results corroborate the findings from 2006, 2012, and 2016 MICS, which found that Thai children under the age of five whose parents had higher education levels engaged in more parental interactions (81%, 96%, and 97%, respectively) [ 15 , 16 , 17 ]. Higher parental education likely creates parental awareness and responsiveness to the children’s natural needs and demand for plays [ 21 , 22 ]. Moreover, educated parents seem to have the ability to obtain specific information about their children’s health requirements [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher parental education likely creates parental awareness and responsiveness to the children’s natural needs and demand for plays [ 21 , 22 ]. Moreover, educated parents seem to have the ability to obtain specific information about their children’s health requirements [ 21 , 22 ]. Higher education levels of parents also help increase parental involvement in child-rearing practice, and the time used with children is likely to be involved with a more developmentally appropriate academic-related activity [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature shows wide socioeconomic (SES) gaps in both the quality and quantity of time parents spend interacting with children, with much of this literature focusing on gaps by parent education rather than household income (Caucutt et al, 2020 ; England & Srivastava, 2013 ; Gershenson, 2013 ; Kalil et al, 2012 ; Vinopal & Gershenson, 2017 ). Over the last few decades, mother–child and father-child time has increased, and SES gaps in developmental or enriching activities have narrowed, but some gaps in young children’s experiences, including parental engagement with children, persist (Bassok et al, 2016 ; Prickett & Augustine, 2021 ). Evidence suggests that while some gaps by parental education in parent-young child activities such as visiting libraries have narrowed over the past quarter-century, others, such as reading to children or teaching them numbers, have increased (Kalil et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%